Advances in processing and utilization of forest products - Rousseau, Ronald W. (American Institute of Chemical Engineers symposium series, 1974)
Papers presented at the Seventy -seventh National Meeting of the American Institute of Chemical Engineers in New Orleans in 1973 or the Fourth Joint Chemical Engineering Conference in Vancouver in 1973.